2010
DOI: 10.1186/1471-2407-10-455
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species comparison of aCGH data from mouse and human BRCA1- and BRCA2-mutated breast cancers

Abstract: BackgroundGenomic gains and losses are a result of genomic instability in many types of cancers. BRCA1- and BRCA2-mutated breast cancers are associated with increased amounts of chromosomal aberrations, presumably due their functions in genome repair. Some of these genomic aberrations may harbor genes whose absence or overexpression may give rise to cellular growth advantage. So far, it has not been easy to identify the driver genes underlying gains and losses. A powerful approach to identify these driver gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
3
28
1
Order By: Relevance
“…Subsequently, it has been found that the total number of CNAs, also referred to as the chromosomal instability (CIN) score or the genomic instability index, differs between BRCA-associated familial cancers and sporadic tumors. Mainly BRCA1-mutated breast tumors were observed to have the highest number of CNAs compared to other tumors [198][199][200]. Furthermore, the type of CNAs differed between familial and sporadic tumors, with a higher frequency of large deletions being present in the BRCA-mutated breast cancers [199].…”
Section: Dna Copy Number Aberrationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Subsequently, it has been found that the total number of CNAs, also referred to as the chromosomal instability (CIN) score or the genomic instability index, differs between BRCA-associated familial cancers and sporadic tumors. Mainly BRCA1-mutated breast tumors were observed to have the highest number of CNAs compared to other tumors [198][199][200]. Furthermore, the type of CNAs differed between familial and sporadic tumors, with a higher frequency of large deletions being present in the BRCA-mutated breast cancers [199].…”
Section: Dna Copy Number Aberrationsmentioning
confidence: 96%
“…It has been shown in multiple studies that BRCA1-and BRCA2-mutated breast cancers display characteristic DNA copy number gains and losses [165,[198][199][200]. Subsequently, it has been found that the total number of CNAs, also referred to as the chromosomal instability (CIN) score or the genomic instability index, differs between BRCA-associated familial cancers and sporadic tumors.…”
Section: Dna Copy Number Aberrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent cross species comparison study [6] our algorithm was used successfully to compare mouse to human aCGH data, showing the wide range of datasets our method can be applied to. For a more in depth analysis and comparison of KC-SMARTR to other methods we made use of a publicly available aCGH dataset [7] consisting of copy number profiles of cell lines derived from B- and T-cell lymphoma's.…”
Section: Resultsmentioning
confidence: 99%
“…As such, whole-exome and whole-genome sequencing approaches have been used to characterize the mutational landscapes of Kras -mutant mouse skin squamous cell carcinoma [71] and Egfr -, Myc - and Kras -driven lung cancers [72,73]. Similarly, whole-exome sequencing, RNA sequencing and DNA copy-number-based approaches have identified several driver genes in mouse models of Brca1 - and Brca2 -deficient breast cancer [74,75].
Figure 3.De novo driver gene identification in mice.
…”
Section: Identifying Cancer Drivers In Mouse Modelsmentioning
confidence: 99%